Typographic design form and communication - Carter, Rob; Maxa, Sandra; Sanders, Mark (Mark Allen); Meggs, Philip B.; Day, Ben (Hoboken, New Jersey Wiley, 2018)
"This book is the definitive reference for graphic designers, providing a comprehensive introduction to the visual word. Done well, type can communicate so much more than the words themselves; in fact, the written words and the "real" message can be at odds. Typography design determines how you feel about a message, the associations you make, and ultimately, the overall success of the piece. Typography design extends from the page to the screen, and is a critical element of almost any graphic design project. This book provides essential guidance on everything related to type: from letterforms and negative space, to messaging, processes, and history, aspiring designers will find great utility in mastering these critical concepts"--Provided by publisher.
The evolution of typography -- The anatomy of typography -- Legibility -- The typographic grid -- Syntax and communication -- The typographic message -- The evolution of typographic technology -- Typography in time and motion -- Case studies in typographic design -- Typographic design education -- Typographic design process -- Type specimens.
Includes bibliographical references and index.
Keywords: Graphic design (Typography)